Potensi Bakteri Endofit Dalam Menekan Pertumbuhan Phytophthora Palmivora (Butler) Secara In Vitro - SUSAN CAMILA FOEH; I GEDE RAI MAYA TEMAJA; KHAMDAN KHALIMI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Potential of Endophytic Bacteria in Suppressing The Growth of Phytophthorapalmivora (Butler) in Vitro The purpose of this study was to determine the potential of endophytic bacteria in controlling cocoa fruit rot caused by the fungus Phytophthora palmivora. The studywas conducted in vitro and direct test on cocoa fruit. The results of the inhibitory testshowed that 4 isolates of endophytic bacteria had the best inhibition for suppressingthe growth of Phytophthora palmivora. The in vitro inhibitory test showed, thetreatment of TN41 isolates was able to inhibit Phytophthora palmivora with thehighest inhibition percentage of 92.52% when compared to the control at theobservation of 5 days after inoculation. The direct test on cocoa fruit showed thetreatment of TN41 isolate had the least area of spot that is 0.20 mm2 at 7 days after inoculation. Further research needs to be conducted related to the stability ofendophytic bacteria isolate TN41 as an antagonist agent against Phytophthorapalmivora.